Faktor pengaruh purchase intention pada fastfood Burger King: peran dari brand equity - Goh, Angelina; Candy, Candy (Universitas Kristen Maranatha, 2022)
Research on the factors that influence purchase intention at Burger King in Batam City was carried out with the aim of testing the significance of brand awareness, brand loyalty, and perceived quality of purchase intention mediated by brand equity. This study was carried out using descriptive statistical and verificative methods which obtained 234 respondents. The research sample was obtained using purposive sampling and Likert scale measurements. Respondents were collected by filling out Google Forms by people who made purchases of Burger King fast food products in Batam City. The data from the study were then processed using Partial Least Square (PLS) and SmartPLS 3.0 software. The results of the study stated that there was a significant positive effect between brand awareness, brand loyalty, and perceived quality on brand equity. There is also a significant positive effect on the influence of the variables of brand awareness, brand loyalty, and brand equity on purchase intention. Then the brand equity variable has a significant influence in mediating the variables of brand awareness, brand loyalty, and perceived brand quality on purchase intention. However, there is no significant effect between perceived quality and purchase intention. This may indicate that perceived quality received by consumers is able to contribute to the assessment of brand equity but does not always lead to having a purchase intention.